The Polemical Context of Gregory of Nyssa's Doctrine of Divine Infinity - Weedman, Mark (Journal of early Christian studies, 2010)
Gregory of Nyssa's account of divine infinity is one of his most important contributions to early Christian thought, so much so that modern scholarship has largely accepted Ekkehard Mühlenberg's claim that Gregory's formulation of the doctrine has no real philosophical or theological antecedent. However, this scholarship has discounted some important evidence to the contrary, especially that of Hilary of Poitiers, who uses an account of divine infinity in ways that anticipate Gregory's. The value of this evidence is that it helps establish the polemical rationale for why Gregory developed and employed divine infinity as he did: to defend the traditional pro-Nicene account of the Son's eternal generation against anti-Nicene (here Eunomian) claims to the contrary.